2006
DOI: 10.1590/s0102-86502006000200006
|View full text |Cite
|
Sign up to set email alerts
|

The number of podocyte and slit diaphragm is decreased in experimental diabetic nephropathy

Abstract: PURPOSE: To determine the number of podocyte, slit diaphragms, slit diaphragm extensions and GBM thickness in diabetic nephropathy. METHODS: Sixty "Rattus Wistar"of both sexes weighing 200-300g were divided in two experimental groups: normal group 10 animals, and alloxan diabetic rats - 50 animals. Alloxan was administered in a single IV dose of 42mg/kg body weight. Body weight, water and food intake, diuresis, and blood and urine glucose were determined in both groups before alloxan injection and two weeks, s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
13
0
1

Year Published

2007
2007
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 14 publications
(16 citation statements)
references
References 17 publications
2
13
0
1
Order By: Relevance
“…GBM thickness increases from 6 months after diabetes induction, and its long-term increase in diabetic rats has been previously reported by Lerco et al [29]. Our study lasted for two weeks, compared with six months in the study of Lerco et al [29].…”
Section: Discussionsupporting
confidence: 74%
See 2 more Smart Citations
“…GBM thickness increases from 6 months after diabetes induction, and its long-term increase in diabetic rats has been previously reported by Lerco et al [29]. Our study lasted for two weeks, compared with six months in the study of Lerco et al [29].…”
Section: Discussionsupporting
confidence: 74%
“…Our study lasted for two weeks, compared with six months in the study of Lerco et al [29]. In our study there was no significant decrease in the thickness of the basal membrane in the DM + EP group, which led us to wonder whether non-treatment of GBM thickening totally with EP may be the effect of a long lasting complication of STZ induction.…”
Section: Discussionmentioning
confidence: 54%
See 1 more Smart Citation
“…The role of glycemic control in renal lesions was investigated herein. In a previous work, we used electron microscopy to study alloxan diabetic rats for 48 weeks, and demonstrated the presence of significant proteinuria, reduction in podocyte number, and increased GMB thickness 6 . In this study, glycemic control attenuated glomerular changes; GBM thickness was not so intense 6 and 12 months after diabetes induction and the podocyte number at 12 months was similar to that in normal animals when continuously using insulin combined with an oral antihyperglycemiant.…”
Section: Discussionmentioning
confidence: 99%
“…Reduced podocyte number has been seen after 6 months in rats with streptozotocin (STZ)-induced diabetes, compared with normal rats 4,5 . In alloxan diabetic rats an evident podocyte reduction has been observed concomitantly with an increased excretion of protein in urine 12 months after induction 6 . There is an inverse relationship between glucose homeostasis an renal damage 7,8 .…”
Section: Introductionmentioning
confidence: 94%